A case of repeated accidental inhalation contamination of a male subject with 137Cs - Hölgye, Z; Malý, M (Health physics, 2002)
Two consecutive incidents of internal contamination occurred within a 13-mo period when a male worker (56 y, 70 kg) briefly entered and stayed (during a breakdown of control apparatus for air contamination) in a radioisotope storeroom with air contaminated by an explosion of old ampules containing 137Cs solution. Monitoring of the first contamination began on day 34 and that of the second one within 1 h after inhalation. According to the two-exponential model, long-term biological half-times of 92 and 93 d were obtained for the first and second contaminations, respectively. The short-term biological half-time for the second contamination was calculated as 3.0 d. The mean value of the fraction of 137Cs excreted in daily urine to that in total excreta was 0.88 for the first contamination and 0.89 for the second one.
Keywords: Administration, Inhalation; aplikace inhalační; radioizotopy cesia; pracovní nehody; Time Factors; Česká republika; Middle Aged; mužské pohlaví; Czech Republic; Body Weight; poločas; Cesium Radioisotopes; Humans; Occupational Exposure; pracovní expozice; tělesná hmotnost; časové faktory; lidé středního věku; Half-Life; Accidents, Occupational; lidé; Male